2000
DOI: 10.1348/000709900157976
|View full text |Cite
|
Sign up to set email alerts
|

The role of repetition in the processes of memorising and understanding: A comparison of the views of German and Chinese secondary school students in Hong Kong

Abstract: While the findings of this study cannot be considered definitive, it is suggested that the emphasis on attentive effort among HKC students is consistent with a traditional, Confucian perspective on learning. The results also indicate that 'the intention to both memorize and understand', found in previous investigations of the study approaches of HKC students, may arise out of being simultaneously aware of two possibilities inherent in repetition: creating a deep impression on the mind and discovering new meani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
110
1
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(121 citation statements)
references
References 11 publications
8
110
1
2
Order By: Relevance
“…Similar to Western students they approach learning with the intention of understanding, however, due to fast teaching pace in class, the process of understanding knowledge starts in class but more importantly continues in evening class and sometimes outside school where they practise questions, read relevant books, think through problems, seek personal meaning and apply their knowledge. This finding supports the claim that, whereas Western students typically see understanding as usually a process of sudden insight, Chinese students tend think of understanding as a long process often requiring considerable effort (Dahlin & Watkins 2000). The survey also demonstrates how much students dislike memorising without understanding.…”
Section: Summary and Discussionsupporting
confidence: 80%
“…Similar to Western students they approach learning with the intention of understanding, however, due to fast teaching pace in class, the process of understanding knowledge starts in class but more importantly continues in evening class and sometimes outside school where they practise questions, read relevant books, think through problems, seek personal meaning and apply their knowledge. This finding supports the claim that, whereas Western students typically see understanding as usually a process of sudden insight, Chinese students tend think of understanding as a long process often requiring considerable effort (Dahlin & Watkins 2000). The survey also demonstrates how much students dislike memorising without understanding.…”
Section: Summary and Discussionsupporting
confidence: 80%
“…In each culture, these culturally based learning orientations (diligence/ persistence for Japanese children and independence/originality Volume 14-Number 4 for U.S. children) predicted children's school achievement in 5th and 6th grade: Those U.S. students who showed higher levels of independence/originality than their own peers in kindergarten also showed higher achievement in later grades; the Japanese students who showed higher levels of diligence/persistence likewise showed higher achievement than their peers. Dahlin and Watkins (2000) also found that Chinese students used memorization (hard work and commitment) and repetition (i.e., diligence) more than their British peers did, and they used these learning activities for different purposes. British students viewed understanding as a process of sudden insight (i.e., mind orientation), and they used repetition to check their memory.…”
Section: Individuals' Learning Orientationsmentioning
confidence: 93%
“…Several researchers have carried out cross-cultural, qualitative studies to better understand the study habits and conceptions of learning among students from different cultural backgrounds (e.g. Charlesworth 2008;Dahlin and Watkins 2000;Kennedy 2002;Manikutty et al 2007;Valiente 2008). In many studies attempts to memorise, yet high achievement, have been widely attributed to Asian students (Kember 1996(Kember , 2000.…”
Section: Introductionmentioning
confidence: 99%